Integration of machine learning and CFD for modeling mass transfer in water treatment using membrane separation process - Kamal Y. Thajudeen; Mohammed Muqtader Ahmed; Saad Ali Alshehri (Scientific Reports, 2024)
Abstract This study aims to assess the efficacy of machine learning models in predicting solute concentration (C) distribution in a membrane separation process, using the input parameters which are spatial coordinates. Computational fluid dynamics (CFD) was employed with machine learning for simulation of process. The models evaluated include Kernel Ridge Regression (KRR), Radius nearest neighbor regression (RNN), K-nearest neighbors (KNN), LASSO, and Multi-Layer Perceptron (MLP). Additionally, Harris Hawks Optimization (HHO) was utilized to fine-tune the hyperparameters of these models. Leading the way is the MLP model, which achieves a remarkable test R2 value of 0.98637 together with very low RMSE and MAE values. Strongness and generalization capacity are shown by its consistent performance on test and training datasets. To conclude, the effectiveness of using machine learning regression methods more especially, KRR, KNN, RNN, LASSO, and MLP in estimating concentration from spatial coordinates was demonstrated in this work. For separation science via membranes where predictive modeling of spatial data is essential, the results offer important new perspectives by developing hybrid model.